프랑스와 한국의 생물다양성 정책수단 비교 연구 : 토지소유자 대상의 생물다양성 계약을 중심으로 - 이유현 (한국비교정부학보, 2020)
(Purpose) Biodiversity policy is a term refers to a policy of securing diversity of species and utilizing resources. In the meantime, Korea has been evaluated for its lack of proper management. One of the key policy instrument in Korea's biodiversity policy is the biodiversity contract system. However, it is necessary to improve the current system to enhance its effectiveness. (Design/methodology/approach) This paper analyzes the biodiversity contract system in France and Korea and suggests implications to improve the Korean biodiversity contract system by using qualitative case studies with descriptive and comparative perspective. (Findings) Based on the results of the analysis, several suggestions were made as follows. First, expand the scope of policy instrument, second, diversification of compensation methods, and third, consideration of mainstreaming of biodiversity. (Research implications or Originality) This paper is particularly meaningful in recalling the importance of domestic biodiversity policy which has been underestimated. As a result of comparative analysis, the process of choosing the policy instruments of the two countries differed in ideology, interests, beneficiaries, and path dependency. In addition, differences were explored between the two countries in terms of the legal basis, purpose of the contract, actual operation, actual benefits of the contract, and the duration.
Keywords: Biodiversity Policy; French Policy; Policy Instrument; Biodiversity Contract; 생물다양성 정책; 프랑스 정책; 정책수단; 생물다양성 계약